The wolf and his king - Longman, Finn (Erewhon, an imprint of Kensington Publishing Corp., 2026)
Step into the resplendent courts and forests of medieval Brittany in this spellbinding retelling of the 12th-century tale of Bisclavret the werewolf. The wolf-sickness strikes always without warning, stealing Bisclavret's body and confusing his mind. Since boyhood, he hasn't dared leave his isolated holdings not to beg the return of his father's lost estate, not to seek brotherhood among the court, not even to win the knighthood he yearns for. But when a new king ascends, Bisclavret must deliver his kiss of fealty or answer for the failure. Half an exile himself, the young king is intrigued by this uneasy, rough-hewn nobleman. Bisclavret seems a perfect knight: bold, strong, and merciful. But he keeps his secrets close, and the king's longings are not for counsel alone. As his fascination grows, the barriers between them multiply, until one day Bisclavret vanishes beyond reach. Battling desperation and grief, the king stands alone to face the greatest threats to his kingdom, with only duty to his people between him and ruin duty, and the steadfast loyalty of the strangest wolf.